The Effectiveness of MONOGAMIA (Monopoly to Prevent Anemia) on Female Adolescent Knowledge about Anemia Prevention and Consumption of Iron Supplement - Aprianti, Nurannisa Fitria; Sari , Apriani Susmita (Babali Publisher, 2024)
Introduction: The leading causes of anaemia in female adolescents are iron and nutrient deficiencies, excessive blood loss during menstruation, and incorrect diet due to a lack of knowledge of female adolescents about the prevention of anaemia and the consumption of iron supplement tablets. This study aimed to analyse the effectiveness of MONOGAMIA on the knowledge level of female adolescents.Methods: The research design was a quasi-experiment pre-post-test with control group. The sample was 96 female students divided into two groups at Senior High School East Lombok from October 4-14, 2024. The intervention group used MONOGAMIA, and the control group used the CEMARI Flip Chart. The Fe tablet was given for four weeks. Data collection used questionnaires of knowledge and iron supplement consumption compliance cards. Knowledge pre-test and post-test were taken on the same day in both groups, and compliance with iron consumption was taken one week after education. The research data were analysed using Wilcoxon, Mann Whitney, and Chi-Square (α<0.05). Results: Both groups had a significant difference in knowledge of anaemia prevention before and after education (p<0.001). There was a significant difference in knowledge about anaemia prevention after education between two groups (p = 0.000). There was a significant difference in iron supplement consumption between the intervention and control group after education (p = 0.028). Conclusion: MONOGAMIA is more effective in increasing knowledge about anaemia prevention and iron supplement consumption in female adolescents than CEMARI. MONOGAMIA can be used to educate female adolescents on how to prevent anaemia.